Comparison of the self-piloting constructive and destructive interference in 7 and 23 GHz band over the seawater surface - Elmutasima, Imadeldin Elsayed; Izzeldin Ibrahim, Mohamed Abdelaziz (Institute of Electrical and Electronics Engineers Inc., 2021)
Autonomous technology is tremendously evolving modern life and expected to transform the world utterly. Different aspects for ground-air space connection need various frequencies to support the high capacity, tremendous data rate, and unmistakably link connection. The present frequency bands reach their capacity limit and consider below the customer's demands particularly when thinking about the new upcoming technologies such as IoT and Unmanned Aerial Vehicle (UAV) technologies. In this work, we investigate propagation characteristics of the radio channel in 7 and 23 GHz as a part of the new super-high frequency (SHF) band which is expecting to operate for wireless control and particularly above the seawater surface that is considered an unusual environment from the link connection point of view. The two frequency bands were selected based on their utilization in various link budgets to cover the effect of frequency in terms of different wireless conceptual such as constructive and destructive Interference behavior in addition to the vertical and horizontal polarization. The result shows that the 23 GHz is severely affected by the path loss propagation with extremely high variation in constructive and destructive interferences which could be accommodated when using space diversity technology. The scientific approach of the study estimates the potential analysis to overtake the challenges of new era demands.